The use of accelerometry to evaluate the BMX cycling starting hill. Effect of the Q-Ring™ on the acceleration profile - Elvira, J. L. L.; Mateo-March, M.; Zabala, M.; Blasco-Lafarga, C. (Sports Biomechanics, 2023)
Accelerometers are becoming popular in sport performance, as they are easy to wear, affordable, and usable in the field. Eccentric chainrings have been commercialised to improve pedalling performance, but little is known about their possible effects in the first pedal strokes (PS) of maximal sprint starts. To analyse the effects of the Q-Ring chainring (Q) on pedalling mechanics and performance in the BMX starting hill, 12 Spanish-National-Team BMX athletes performed 3 maximal sprints comparing Q vs No-Q. Time was measured in the first three meters. Acceleration output was registered with a triaxial 6 g accelerometer (200 Hz) in the first four PS. Discrete time, acceleration and statistical parametric mapping (SPM) were used to compare between conditions. Q showed no improvement in performance, despite a force-application time increasing (p = 0.013, ES = 0.39) and a reduction in the dead spot time (p = 0.028, ES = -0.73). Time after the four PS was greater (p = 0.006, ES = 0.63), and 3-m time did not change. Likewise, SPM 1D comparison showed no differences along the four PS. Therefore, accelerometry confirms its potential to evaluate pedalling technique in BMX, where Q-Ring fails to improve the pedalling mechanics in the starting hill.